Contributions to Nephrology 2006
DOI: 10.1159/000096757
|View full text |Cite
|
Sign up to set email alerts
|

A History of the Kidney in Plasma Cell Disorders

Abstract: Historical understanding of the kidney in plasma cell disorders reflects developments in understanding of the anatomy and physiology of the kidneys in health and in disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Several reports have noted that DRA is related to the duration of HD and can be cured by kidney transplantation. 1,7,12) In this case, the amorphous amyloid materials infiltrated not only into the extensor and flexor tendons but also into the wrist joint. In the operation, clear identification and separation of amyloid body from the tendon was very difficult.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Several reports have noted that DRA is related to the duration of HD and can be cured by kidney transplantation. 1,7,12) In this case, the amorphous amyloid materials infiltrated not only into the extensor and flexor tendons but also into the wrist joint. In the operation, clear identification and separation of amyloid body from the tendon was very difficult.…”
Section: Discussionmentioning
confidence: 79%
“…The term "amyloid" was first used by the pathologist Rudolf Virchow, who described such deposits as comprising cellulose-like material. 1) Meanwhile, dialysis-related amyloidosis (DRA), also known as β-2 microglobulin amyloidosis, is a specific subtype of amyloidosis that is commonly seen in endstage renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…The species of Aspergillus that cause invasive infection are limited, but these share an important trait: the ability to grow at 37°C, human body temperature. Among those that cause invasive disease in humans, A. fumigatus is the most prevalent followed, by A. flavus (1,2). Despite constant contact with conidia, the immunocompetent host rarely develops invasive disease, largely because immune defenses in lungs are highly effective.…”
Section: Nadph Oxidase Regulates Efficacy Of Vaccination In Aspergillmentioning
confidence: 99%
“…Chief among them are the use of glucocorticoids to treat inflammatory disorders, severe neutropenia induced by cytotoxic agents, or, less frequently, the use of TNF-a antagonists. The risk of disease acquisition escalates in parallel with the length of glucocorticoid administration or the duration of neutropenia (1). Qualitative defects in neutrophil function also increase the probability of acquiring disease.…”
Section: Nadph Oxidase Regulates Efficacy Of Vaccination In Aspergillmentioning
confidence: 99%
“…In honor of his work, the M-LC was later named the Bence Jones protein (BJP). Advances in electrophoresis technique allowed for the separation of serum proteins into three major bands, α, β, and γ [4]. In 1956, Korngold and Lipari demonstrated that the BJP actually contained two antigenic separate types of 7-S globulin which were later named κ and λ in their honor [5].…”
Section: Introductionmentioning
confidence: 99%